Merancang Konten Instagram Ads Sebagai Solusi Pemasaran Digital Pada Indibiz PT Telkom - Nusopa, Imelda Paranata; Wibowo, Sampurno (Eqien - Jurnal Ekonomi dan Bisnis, 2024)
The development of information and communication technology has bought significant impacts in various aspects of human life, including in terms of connectivity and access to information. The utilization of internet-based digital technology for marketing products or services to consumers is growing, one of which is through the Instagram application. Digital marketing is the process of promoting and finding markets through social network-based digital media. This research aims to design Instagram Ads content as a digital marketing solution at Indibiz PT Telkom, focusing on the promotion of products and services. The method used in descriptive qualitative, with data obtained through interviews and observations. The results showed that creative and interactive promotional content on Instagram can increase consumer engagement and contribute to increases sales. Keywords: Digital Marketing, Instagram Ads, Content